2008
DOI: 10.1038/sj.bjc.6604536
|View full text |Cite
|
Sign up to set email alerts
|

A randomised multicentre phase II trial of capecitabine vs S-1 as first-line treatment in elderly patients with metastatic or recurrent unresectable gastric cancer

Abstract: This randomised multicentre phase II study was conducted to investigate the activity and safety of two oral fluoropyrimidines, capecitabine or S-1, in elderly patients with advanced gastric cancer (AGC). Elderly (X65 years) chemo-naive patients with AGC were randomly assigned to receive capecitabine 1250 mg m À2 two times daily on days 1 -14 every 3 weeks or S-1 40 -60 mg two times daily according to body surface area on days 1 -28 every 6 weeks. Ninety-six patients were enrolled and 91 patients were randomise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 37 publications
5
102
0
2
Order By: Relevance
“…Lee et al [24] and Koizumi et al [25] reported the following incidences of grade 3/4 toxicities: decrease in serum hemoglobin, 9%-14.3%; anorexia, 9.5%-12%; and nausea, 4.8%-6%. These data are similar to those in the middle-aged group in the present study (decrease in serum hemoglobin, 18%; anorexia, 6%; nausea, 5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al [24] and Koizumi et al [25] reported the following incidences of grade 3/4 toxicities: decrease in serum hemoglobin, 9%-14.3%; anorexia, 9.5%-12%; and nausea, 4.8%-6%. These data are similar to those in the middle-aged group in the present study (decrease in serum hemoglobin, 18%; anorexia, 6%; nausea, 5%).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [24] conducted a randomized phase II study comparing capecitabine and S-1 in patients older than 65 years, and showed satisfactory effi cacy of S-1 (RR, 29%; median time to progression, 4.2 months; median OS, 8.1 months). In Japan, Koizumi et al [25] conducted a phase II study of S-1 in patients older than 75 years and demonstrated a RR of 21%, median PFS of 3.9 months, and median OS of 15.7 months.…”
Section: Discussionmentioning
confidence: 99%
“…Although the most commonly used first-line chemotherapy regimen was fluoropyrimidine with/without platinum (60-75 %) [15][16][17][18][19][20][21][22][23], some feasible patients, who had good performance or low tumor burden such as isolated para-aortic lymph node metastasis, were treated with a triplet regimen including taxane, fluoropyrimidine and platinum [26][27][28]. Those were about 8 % of all patients (290 patients) over all the periods, and their survival outcome of 7.8 months in PFS (95 % CI 7.0-8.6 months) and 14.0 months in OS (95 % CI 12.6-15.4 months) was not significantly different among the three periods (p = 0.485, p = 0.512, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used firstline cytotoxic chemotherapy agent was fluoropyrimidine with/without platinum: 579 (65.8 %) in period 1, 1083 (68.8 %) in period 2 and 1153 (80.3 %) in period 3. The most commonly used first-line chemotherapy regimen was fluoropyrimidine with/without platinum (60-75 %) [15][16][17][18][19][20][21][22][23], and taxane-based chemotherapy was most commonly used as second line (50 %) [24,25]. A triplet regimen including taxane, fluoropyrimidine and platinum was administered to *8 % of patients over all periods [26][27][28].…”
Section: Betweenmentioning
confidence: 99%
“…Given the large numbers of trials and the many different comparisons in the trials retrieved, the gi dsg made an a posteriori decision to focus on the individual contributions of fluoropyrimidines 20,24,25,28,[32][33][34][35][36][37][38][39][40] , platinum agents 9,23,26,30,36,[41][42][43][44][45] , anthracyclines 34,46 -50,79 , taxanes 22,51,52 , and irinotecan 9,53 . The dsg also decided to determine whether the available evidence supports the regimens that are currently in common use in Ontario 21,24,25,36,48,[55][56][57][58] and to determine the contribution of targeted therapies 59,80 .…”
Section: Resultsmentioning
confidence: 99%